Autocrine growth regulation by granulocyte colony-stimulating factor and granulocyte macrophage colony-stimulating factor in human gliomas with tumor progression - Müller, Margareta M.; Herold-Mende, Christel; Steiner, Hans H.; Fusenig, Norbert (The American journal of pathology, 1999)
Granulocyte colony-stimulating factor (G-CSF) and granulocyte macrophage colony-stimulating factor (GM-CSF) and/or their receptors are increasingly detected in solid human tumors, although little is known about their function in tumor growth and invasion. We analyzed RNA and protein expression of both factors and their receptors in 22 human gliomas (WHO grade II, III, and IV) and derived cell cultures. G-CSF, GM-CSF, and/or their receptors were expressed in all tumors and derived cell cultures, but coexpression of both factors and receptors was almost exclusively found in grade IV glioblastomas and thus correlated with advanced tumor stage. The functional significance of G-CSF and GM-CSF as regulators for glioma cells was demonstrated by 1. stimulation of proliferation and migration in tumor cells expressing one or both receptors by the corresponding factor; 2) inhibition of growth and migration of glioma cells expressing G-CSF, GM-CSF, and their receptors by neutralizing antibodies to both factors. These results indicate a significant role for both factors in the autocrine regulation of growth and migration in late-stage malignant gliomas and suggest a shift from paracrine to autocrine regulation with tumor progression. The implication of G-CSF and GM-CSF in glioblastoma growth regulation could make these factors further prognostic indicators and raises questions concerning their use in cancer therapy.